Potentiometric Analysis of Samarium Ion in Aqueous Solution Employing Selective Electrode Based on Crown Ethers - Samarium Picrate Complexes in a PVC Membrane - Karim, N. H.; AI- Nuaimi, S.A.; Nassory, N. S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Samarium ion selective electrodes we1Â·e construct.ed and prepared then tested as probefor Samarium ion detection and determination in different aqueous solutions. The sensitive membrane is made of PVC which contains Samarium picrate complexed with either 18-crown-6 or 15-crown-5 ethers as active species. Different plasticizers: phthalates (DBPH), phosphates (DBP) and phosphonates (DOPP) were incorporated into the membranes as solvent mediators. Every membrane was evaluated practically following standard proced ures to find out its reliability and durability as a probe suitable for analytical application. Linear working range, Ncrnestain slope, detection l imit, measurement stability, response time and electrode l ife tirnc were calculated for each electrode. The l inear concentration range for most ol’the electrodes were from - _, 10 to 10 molar Sm (III), the slope was 18 mv/decade to 20 mv/decade whi l e the working pH range was from 3 to 8. Cations interference and anion radicals Na+, Ca2+, La"+, Nd ’+ have no effect on the measurement selectivity except in the presence M (Ill) ions.